Association Between Daily Dietary Eicosatetraenoic Acid Intake and the Lower Risk of Psoriasis in American Adults - Zhan J; Tang X; Wang F; Han J (Dove Medical Press, 2021)
Jipang Zhan, Xuhua Tang, Fang Wang, Jiande Han Department of Dermatology, the First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 510080, People's Republic of ChinaCorrespondence: Jiande HanDepartment of Dermatology, the First Affiliated Hospital of Sun Yat-sen University, No. 58 Zhongshan Second Road, Guangzhou, Guangdong, 510080, People's Republic of ChinaTel +86-138-0274-3924Fax +86-020-8293-8840Email hanjd@mail.sysu.edu.cnPurpose: Unlike eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the relationship between eicosatetraenoic acid (ETA) and psoriasis remains unclear. Therefore, We performed a cross-sectional study in the general American population to investigate the association between daily dietary ETA, EPA, and DHA intake and the risk of psoriasis.Participants and Methods: This study applied data from the National Health and Nutrition Examination Survey (NHANES) 2003- 2006 and 2009- 2014. Dietary n3 polyunsaturated fatty acids (PUFA) were calculated based on two 24-hour dietary recall interviews. We defined psoriasis by responding to the question "Have you ever been told by a doctor or other health care professional that you had psoriasis?". Multivariable logistic regression analysis, trend tests, subgroup analysis, and interaction tests were used to evaluate the associations of ETA, EPA, and DHA intake with the risk of psoriasis, respectively.Results: A total of 15,733 participants were included in this study. In our optimal multivariate-adjusted model, the odds ratio (OR) with 95% confidence interval (CI) of psoriasis were 0.30 (0.12, 0.88), 1.92 (0.78, 4.74), 1.28 (0.72, 2.27) for daily dietary ETA, EPA, and DHA intake, respectively. Trend tests showed a dose-effect relationship between daily dietary ETA intake and the lower risk of psoriasis. Subgroup analysis and tests for interaction showed that the association was stable in different subgroups.Conclusion: Our study revealed that there might be a dose-effect association of daily dietary ETA intake with the lower risk of psoriasis in American adults.Keywords: psoriasis, diet, eicosatetraenoic acid, long-chain n3 polyunsaturated fatty acid, NHANES